Stan inteligencji środowiskowej studentów z Polski, Słowacji, Czech i Ukrainy - Cynk, Kaolina (Kultura-Społeczeństwo-Edukacja, 2018)
Article consists from two part – theoretical, which contain conceptualization of basic concepts and empirical, in which have been presented investigative hypotheses and analysis of the data obtained results conducted research in Poland, Slovakia, Czech Republic and Ukraine in 2015. The subject of the research was: “Environmental values in the awareness of the students of humanities and life sciences from the selected European countries”. Formulate conclusions are pessimistic enough. They indicate, that level of evolution of environmental intelligence is low among students, accompanies also deficit of feature of so called environmental personality ago. The highest level of environmental intelligence have presented non-believers and persons declaring other confession. In second variable they were inhabitants of cities. Results they should present impulse for taking of next research in this range.